Prevalence of Depression and Anxiety among Patients of Pulmonary Tuberculosis in Outpatient TB Clinic of Bahawalpur Medical and Dental College, Bahawalpur (Medical Forum Monthly, 2022)
Objective: The objective of this study is to assess the prevalence of anxiety and depression among patients of pulmonary TB in Bahawalpur City, Punjab, Pakistan where such a study has not been done previously and may prove advantageous in constructing strategies to ensure coordination between physicians, psychiatrists and psychologists in managing both physical and psychological aspects of pulmonary TB leading to overall improved quality of life.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Outpatient TB Clinic of Bahawalpur Medical and Dental Hospital, Bahawalpur, Pakistan for a period of 10 months from 1st December, 2021 to 30th August, 2022.Materials and Methods: Patients aged 18 to 60 years with lab diagnosed primary pulmonary TB receiving anti-TB treatment for less than 3 months were included. Depression and anxiety were assessed by HADS scoring (Hospital Anxiety and Depression Scoring). A cut-off score of 11 or greater was considered clinically significant depression and anxiety. Data analysis was done by Statistical Packages for Social Sciences (SPSS) version22.0.The frequencies of patients were noted and chi square test was applied.Results: The relative frequencies of depression and anxiety are 240 (60%) and 224 (56%). Depression was present in 137 (62.2%) males and 117 (65%) females with a p – value of 0.537. Anxiety was found in 128 (58.2%) males and 115(63.8%) in females with a p- value of 0.2449.Conclusion: Depression and anxiety are quite prevalent among patients with TB, irrespective of gender.